Safe Zone for Insertion of a Fibular Lag Screw in Ankle Fracture Fixation. Issue 3 (14th September 2018) - Mason, Lyndon; Kaye, Angus; Marlow, William; Williams, Geraint; Molloy, Andrew
Category: Ankle Introduction/Purpose: Fibular lag screw placement during ankle fracture fixation is not without risk. The screw placement endangers either the tendons of the peronei or the posterior rim of the incisura if misplaced. Our aim was to identify a predictable safe zone for screw placement. Methods: 45 radiographs of Weber B fractures were reviewed to determine the typical height of lag screw entry and exit points. 63 MRI scans of anatomically normal ankles were reviewed to evaluate tendon position and syndesmosis location. The safe zone could then be determined using composite images. Results: On review of the 45 ankle fracture radiographs; the typical lag screw exit point was found to be 14.2 mm above the ankle joint (95% Confidence Interval: 11.3-17.1 mm). Using the composite MRI images, there was a consistent flat anterior aspect of the fibula at this level. A safe zone trajectory was seen to occur between 31 and 45 degrees taken from the anterior aspect of the flat fibular surface at this level. The minimum distance to at-risk structures using this trajectory was 4 mm. If this consistent entry point is used, the MRI scans demonstrated that if the drill was aimed towards the medial edge of the Achilles tendon, the correct trajectory would be performed. Conclusion: The flat surface of the fibula is a constant landmark on MRI and is visible during surgery. The peroneal tendons and posterior rim of the incisura have a constant predictable position related to this. The safe zone for insertion of a lag screw is between 31 and 45 degrees medial to the anterior aspect of this flat surface. This represents aiming the drill towards the medial aspect of the Achilles tendon.